63+3*4-(2*2*2*2:8+5*6)
Răspunsuri la întrebare
Răspuns de
2
63+3*4-(2*2*2*2:8+5*6)=
63+12-(16:8+30)=
63+12-(2+30)=
63+12-32=
75-32=
43
63+12-(16:8+30)=
63+12-(2+30)=
63+12-32=
75-32=
43
Răspuns de
0
63+3*4-(2*2*2*2:8+5*6)
=63+3*4-(4*2*2:8+5*6)
=63+3*4-(8*2:8+5*6)
=63+3*4-(16:8+5*6)
=63+3*4-(2+30)
=63+12-32
=75-32
=43
=63+3*4-(4*2*2:8+5*6)
=63+3*4-(8*2:8+5*6)
=63+3*4-(16:8+5*6)
=63+3*4-(2+30)
=63+12-32
=75-32
=43
Alte întrebări interesante
Informatică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă